Frequency switchable correlated transports in perovskite rare-earth nickelates. Issue 27 (1st July 2020) - Chen, Jikun; Li, Haifan; Wang, Jiaou; Ke, Xinyou; Ge, Binghui; Chen, Jinhao; Dong, Hongliang; Jiang, Yong; Chen, Nuofu
Abstract : Delta-temperature thermistor functionality in correlated rare-earth nickelates sheds light on regulations for the working state of electronic devices using AC-frequency dependent impedance without altering the materials. Abstract : While electron correlations were previously recognized to result in direct current (DC) transportation properties beyond-conventional ( e.g., metal-to-insulator transitions, bad metal, thermistors), their respective influences on the alternating current (AC) transport are largely overlooked. Herein, active regulation of the electronic functionalities of d-band correlated rare-earth nickelate ( Re NiO3 ) thin films, by simply utilizing their electronic responses to AC-frequencies ( f AC ) is demonstrated. Assisted by temperature dependent near edge X-ray absorption fine structure analysis, positive temperature dependences in the Coulomb viscosity of Re NiO3 were discovered, which moderate their AC impedance ( R ′ + iR ′′). Distinguished crosslinking among R ′– f AC measured in nearby temperatures is observed that differs to conventional oxides. This enables active adjustability in correlated transports of Re NiO3, among NTCR-, T Delta - and PTCR-thermistors, via f AC from the electronic perspective without varying materials or device structures. Furthermore the T Delta – f AC relationship can be widely adjusted via the Re composition and interfacial strains. The AC-frequency sensitivity discovered in Re NiO3 leads the way to a new freedom in regulating and switching the device working states beyond the present semiconductor technologies. It opens up a new model for enriching novel electronic applications in automatic transmission, artificial intelligence in sensing temperatures or thermal perturbations.